2009
DOI: 10.1365/s10337-008-0923-9
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Determination of the Major Constituents in the Traditional Uighur Medicinal Plant Saussurea involucrata by LC-DAD-MS

Abstract: A high-performance liquid chromatography (LC) coupled with diode array detector (DAD) and electrospray ionization mass spectrometry (ESI-MS) method was developed for the simultaneous analysis of the major constituents in Saussurea involucrata (SI). A comprehensive validation of the developed method was conducted, and the unique properties of the present method were confirmed by analyzing eleven SI samples. Seventeen compounds including phenolic acids, flavonoids, and lignanoids were identified by online ESI-MS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 14 publications
0
20
0
Order By: Relevance
“…They describe phenolic acid determination in medicinal plants and preparations, as R. nigrum bud-preparations (Castro et al, 2010;Urpi-Sarda et al, 2009), according to the single bioactive compound concentrations shown in this research. Among other identified classes, flavonols and catechins were also selected for quantitative studies (Huang et al, 2008;Surveswaran et al, 2010;Yi et al, 2009). Based on the obtained results, most of the research pointed out that the identified polyphenolic compounds significantly contribute to the total phytocomplex of these herbal preparations.…”
Section: Discussionmentioning
confidence: 99%
“…They describe phenolic acid determination in medicinal plants and preparations, as R. nigrum bud-preparations (Castro et al, 2010;Urpi-Sarda et al, 2009), according to the single bioactive compound concentrations shown in this research. Among other identified classes, flavonols and catechins were also selected for quantitative studies (Huang et al, 2008;Surveswaran et al, 2010;Yi et al, 2009). Based on the obtained results, most of the research pointed out that the identified polyphenolic compounds significantly contribute to the total phytocomplex of these herbal preparations.…”
Section: Discussionmentioning
confidence: 99%
“…The abundance of chemical constituents differs in herbs obtained from different origins. It is believed that the quality of Snow Lotus sourced from Tianshan of Xinjiang in China (Yi et al, 2009b) is the best of all.…”
Section: Limits Of Indicator Compoundsmentioning
confidence: 99%
“…Total phenolic content was found to be ranging from 23.58 to 41.56 mg/g while the content for total flavonoid is 9.08 and 15.84 mg/g. Other bioactive compounds were qualitatively determined as well, including syringin (0.20-0.58 mg/g), arctiin (0.05-1.62 mg/g), apigenin (0.005-0.015 mg/g) and hispidulin (0.05-0.16 mg/g) (Chen et al, 2013a;Li and Zhong, 2013;Qiu et al, 2010;Xu et al, 2009;Yi et al, 2009b).…”
Section: Phytochemistrymentioning
confidence: 99%
See 2 more Smart Citations